CONTRIBUTION AND PERSPECTIVES OF NEW FLEXIBLE SHAFT COUPLING TYPES – PNEUMATIC COUPLINGS - Jaroslav HOMIŠIN (Scientific Journal of Silesian University of Technology. Series Transport)
The contribution briefly approaches the author’s profile in the field of scientific research during his work at TU in Košice. More precisely, it presents a selected, specific area of torsional oscillation of mechanical systems concerning the characteristics, research and application of new elements, i.e., so-called pneumatic tuners of torsional oscillation (pneumatic couplings), a field that the author has long been devoted to. In the process, the article informs the reader about the development of new types of flexible shaft couplings, i.e., tangential and differential pneumatic couplings (also with autoregulation), presents the results of static and dynamic measurements made on certain couplings with the interconnection of pneumatic flexible elements and draws attention to the conditions involved in the application of these coupling types in torsionally oscillating mechanical systems.